Evaluation of serum resistin levels in Iraqi rheumatoid arthritis patients under biological treatment and their correlated clinical disease activity index - Shatha Sabah Shyaa,; Hanaa Naji Abdullah,; Khalied Yassen Zakair, (Journal of the Pakistan Medical Association, 2023)
Objective: The current study aimed to evaluate RA patients’ serum resistin levels and to observe the relationship between disease activity and resistin. Methods: A case-control study was conducted on (100) RA Iraqi patients during treatment with bDMARDs. The first group of 50 patients received etanercept, and the second group of 50 patients were on Rituximab (RTX). The control group comprised of 50 healthy individuals. ELISA was used to evaluate serum Resistin in and anti-CRP. Inflammatory markers ESR, and CRP with biochemical tests were conducted. In addition to estimating Clinical Disease Activity score I(CDAI) by the physicians; at Baghdad Teaching Hospital. Results: Levels of Resistin of RA treated with RTX were significantly higher (16.30 ± 7.38ng/ml) than in RA treated with ETN (10.61±5.85ng/ml) compared to the control group. (6.95±1.70 ng/ml). The resistin level showed a positive correlation with Anti-CCP abs which was considered to have a high positive correlation (p< 0.01) in ETN group. While this correlation was lower than the RTX group, the, correlation between resistin, and ESR was the highest in RTX group whilst no such correlation was observed in the ETN group. There was a positive correlation with CDAI of RA subgroups (moderate activity (p<0.05), and high activity (p<0.001). The logistic regression of resistin was associated with biological treatment, odds ratio was (OR=1.138, p-value= 0.014, 95% CI.1.025-1.257) during ETN, and RTX independent of CRP. Conclusion: There is an association between serum RSN and anti CRP as a result of disease activity independent of CRP. resist in levels can be used to determine disease activity to avoid disease progression and erosion. Keywords: Protein, Antibodies, Etanercept, Rituximab, Disease, Physicians